Improved Survival with the Patients with Variceal Bleed - Praveen Sharma; Shiv K. Sarin (International Journal of Hepatology)
Variceal hemorrhage is a major cause of death in patients with cirrhosis. Over the past two decades new treatment modalities have been introduced in the management of acute variceal bleeding (AVB) and several recent studies have suggested that the outcome of patients with cirrhosis and AVB has improved. Improved supportive measures, combination therapy which include early use of portal pressure reducing drugs with low rates of adverse effects (somatostatin, octerotide or terlipressin) and endoscopic variceal ligation has become the first line treatment in the management of AVB. Short-term antibiotic prophylaxis, early use of lactulose for prevention of hepatic encephalopathy, application of early transjugular intrahepatic portasystemic shunts (TIPS), fully covered self-expandable metallic stent in patients for AVB may be useful in those cases where balloon tamponade is considered. Early and wide availability of liver transplantation has changed the armamentarium of the clinician for patients with AVB. High hepatic venous pressure gradient (HVPG) >20 mmHg in AVB has become a useful predictor of outcomes and more aggressive therapies with early TIPS based on HVPG measurement may be the treatment of choice to reduce mortality further.